The Plan of the ‘ΝΟΜΙΚΟΣ’ (Luke 10.25–37) - Kilgallen, John J. (New Testament studies, 1996)
At 12.28 Mark speaks of a scribe who asked Jesus ‘What is the first commandment?’ The motive for the scribe's question is not expressed, but from the way the story unfolds (12.28–34), it seems that his question was sincere, straightforward and not devious. It is very unlikely that Luke (10.25–37) was influenced by Mark in details,1 but, if Mark be the principal Lucan source, Mark's story was known to Luke and was likely instrumental, we can say, in Luke's decision to incorporate his own story about a νομικός whose encounter with Jesus has certain affinities with that of Mark's γραμματεύς